2011
DOI: 10.1146/annurev-fluid-121108-145456
|View full text |Cite
|
Sign up to set email alerts
|

Flapping and Bending Bodies Interacting with Fluid Flows

Abstract: The flapping or bending of a flexible planar structure in a surrounding fluid flow, which includes the flapping of flags and the self-streamlining of flexible bodies, constitutes a central problem in the field of fluid-body interactions. Here we review recent, highly detailed experiments that reveal new nonlinear phenomena in these systems, as well advances in theoretical understanding, resulting in large part from the rapid development of new simulation methods that fully capture the mutual coupling of fluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
236
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(248 citation statements)
references
References 73 publications
11
236
1
Order By: Relevance
“…As a side remark in his famous paper on the stability of jets, he showed that an infinite membrane placed in an airflow is always unstable. Of course, the problem becomes more complex when bending rigidity and finite plate dimensions are taken into account (see Païdoussis 2004;Shelley & Zhang 2011, for recent reviews)…”
Section: Introductionmentioning
confidence: 99%
“…As a side remark in his famous paper on the stability of jets, he showed that an infinite membrane placed in an airflow is always unstable. Of course, the problem becomes more complex when bending rigidity and finite plate dimensions are taken into account (see Païdoussis 2004;Shelley & Zhang 2011, for recent reviews)…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there has been considerable research on the basic dynamics of flexible structures like flags, which can be bent, folded, twisted or waved in the air [19][20][21][22][23][24][25][26] . The first experimental study on fluttering behaviour was performed by Taneda 27 with a flag made of various fabrics and shapes, to find a variety of flapping modes (for example, nodeless, one-node, imperfect-node and two-node flutters).…”
mentioning
confidence: 99%
“…Here, we use the average speed of the filament's trailing edge U˜ as a scale of the filament's velocity. The kinematic energy integral approximates on a scale of (6) Taking the filament length L as a reference length and considering a soap film with a width L passes the filament, the fluid kinematic energy is expressed as (7) where is the density of the soap film and d is the thickness of the soap film. The value of d depends on the soap film flow velocity.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…(4), (6), and (7), we get (8) where S = ml/ dL. S is the dimensionless density which is a control parameter in the instability of a flag's flapping.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 1 more Smart Citation